Students’ Psychological Adjustment to Shift-Schooling Ecosystem in Sub-Saharan African Urban Communities - Mensah Anapey, Gideon; Kyeremeh, Rosemary; Abomah, Peter Worlanyo (Journal of Educational, Health and Community Psychology, 2025)
While shift-schooling has been recognized for expanding educational access without large-scale infrastructural investments in marginalized communities, little is known about how adolescents in Sub-Saharan Africa psychologically adjust to these learning environments. These students face developmental challenges related to career aspirations, emotional regulation, and interpersonal relationships. Guided by adaptation theory, this study examined academic adjustment among senior high school students by focusing on psychological well-being indicators such as emotion, social relationships, and attachment. Using a survey research design with a random sample of 270 students, moderate reliability coefficients were recorded for psychological adjustment using the Student Adaptation to College Questionnaire (SACQ). Hypotheses were tested using one-way ANOVA and multiple linear regression via IBM-SPSS version 23. Results revealed that accommodation status significantly impacted psychological adjustment to shift-schooling, and gender differences influenced adjustment outcomes. School attachment and emotional and social adjustment behaviours predicted over 63% of the variance in academic adaptation. The study concluded that urban transportation challenges negatively affected non-residential students’ emotional experiences, particularly among females. These findings underscore the importance of psychological factors in shaping students' perceptions of their learning environments. Emotional and relational counseling interventions are recommended to support adolescents transitioning from basic education to senior high school in Sub-Saharan African urban settings.